Electrical properties and relaxation behavior of Na-doped BaBiNb5O15 ceramics. Issue 2 (15th January 2022) - He, Chan; Wang, Weiguo; Li, Minyan; Wu, Ranfei; Li, Xianyu; Wang, Xinfu; Wang, Dan; Hao, Gangling
Abstract: The electrical performance and relaxation behavior of Na + doped BaBiNb5 O15 compound were investigated. The grain conductivity of the BaBi0.96 Na0.04 Nb5 O15-δ compound is 4.71 × 10 −5 S/cm at 763 K, which is an order of magnitude lower than the parent sample at the same measuring temperature. The highest total conductivity of the BaBi0.96 Na0.04 Nb5 O15-δ and BaBiNb5 O15 sample can reach 1.12 × 10 −4 S/cm and 4.0 × 10 −5 S/cm at 643 K, respectively, which indicates that the slight Na + doping can improve the total conductivity. A dielectric relaxation peak related to thermal activation was observed. The activation energy values are E = 0.47 eV for BaBiNb5 O15 sample, and E = 0.49 eV for BaBi0.96 Na0.04 Nb5 O15-δ sample, which indicates that the relaxation activation energy increases with the Bi 3+ ions partially replaced by Na + ions in the BaBiNb5 O15 compound. In addition, the oxygen relaxation peak position shifts to the low-frequency direction, which indicates that Na + ions doping causes the decrease of oxygen vacancy mobility. The lower oxygen vacancy mobility results in the lower grain conductivity in the BaBi0.96 Na0.04 Nb5 O15-δ sample. After aging for the different time at 773 K, the excellent thermal stability of the BaBi0.96 Na0.04 Nb5 O15-δ sample can be found.